(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Volcanic rock is a designation in geology given to extrusive igneous rocks. One type of igneous rock of interest, in economic terms, is vesicular, since, besides the knowledge of the morphology (positioning, size, direction, and interconnectivity of the vesicles) of these structures within the spill, there is also an economic interest regarding the possibility of this rock as a reservoir of fluids (water and hydrocarbons). In this work, samples of vesicular volcanic rock from the Paraná Basin were studied for their characterization, aiming to contribute to the knowledge of this rock proprieties as a reservoir of fluids. The elements present inside the rocks were identified and quantified by X-ray fluorescence and X-ray diffraction. The dimensions of the vesicles and the interconnection between them could be clearly observed in the reconstructed images of the rocks measured by the third generation gamma-ray industrial tomography technique.